Prevalence of Opioid Dispensings and Concurrent Gastrointestinal Medications in Quebec - Rachel E Williams; Nevzeta Bosnic; Carolyn T Sweeney; Ashlee W Duncan; Kristen B Levine; Michael Brogan; Suzanne F Cook (Pain Research and Management)
BACKGROUND: Opioids are frequently prescribed for moderate to severe pain. A side effect of opioid usage is the inhibition of gastrointestinal (GI) motility, known as opioid-induced bowel dysfunction (OBD). OBD is typically treated prophylactically with laxatives and/or acid suppressants.